Establishing apomorphine treatment in Thailand: understanding the challenges and opportunities of Parkinson's disease management in developing countries. (2nd June 2020) - Bhidayasiri, Roongroj; Phokaewvarangkul, Onanong; Sakdisornchai, Karn; Boonpang, Kamolwan; Chaudhuri, K. Ray; Parsons, Jan; Lolekha, Praween; Chairangsaris, Parnsiri; Srivanitchapoom, Prachaya; Benedierks, Sharon; Panyakaew, Pattamon; Boonmongkol, Thanatat; et al.
ABSTRACT: Introduction: The increasing global burden of Parkinson's disease (PD) poses a particular challenge for developing countries, such as Thailand, when delivering care to a geographically diverse populace with limited resources, often compounded by a lack of expertise in the use of certain PD medications, such as device-aided therapies (DAT). Areas covered: A panel of local, regional, and international PD experts convened to review the unmet needs of PD in Thailand and share insights into effective delivery of DAT, focusing on experience with apomorphine infusion. Despite its proven efficacy and safety, implementation of apomorphine infusion as a new option was not straightforward. This has prompted a range of health-care professional and patient-focused initiatives, led by the Chulalongkorn Center of Excellence for Parkinson's Disease and Related Disorders in Bangkok, to help establish a more coordinated approach to PD management throughout the country and ensure patients have access to suitable treatments. Expert opinion: Overcoming the challenges of education, proficiency, resource capacity and standard of care for PD patients in developing countries requires a coordinated effort both nationally and beyond. The best practices identified in Thailand following the introduction of apomorphine infusion might be helpful for other countries when implementing similar programs.